1986
DOI: 10.1128/aem.51.1.150-156.1986
|View full text |Cite
|
Sign up to set email alerts
|

Activity of an Attached and Free-Living Vibrio sp. as Measured by Thymidine Incorporation, p -Iodonitrotetrazolium Reduction, and ATP/DNA Ratios

Abstract: Three independent techniques, [3H]thymidine incorporation, the reduction rate of p-iodonitrotetrazolium violet (INT) to INT formazan normalized to DNA, and the ratio of ATP to DNA, were adapted to measure the activity of attached and unattached estuarine bacteria. In experiments employing the estuarine isolate Vibrio proteolytica, nutrient concentrations were manipulated by varying the concentration of peptone-yeast extract. In the presence of exogenous nutrients, the activity of free-living cells was greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 34 publications
(40 reference statements)
2
24
0
Order By: Relevance
“…Because the ko, km, and kc o 2 values re p resent a series of mass-transfer and reaction processes occurring within the cell membrane, the dependence on surf a c e a rea likely has a mechanistic basis. Activity decreases with attached bacteria have also been observed in batch assays by other workers [5,25]. Jeffery and Paul [5] found that the thymidine incorporation rate and the ATP/DNA ratio of free suspended cells were greater than those of attached cells.…”
Section: Degradation and Mineralization Of Naphthalene By Attached Cesupporting
confidence: 54%
See 2 more Smart Citations
“…Because the ko, km, and kc o 2 values re p resent a series of mass-transfer and reaction processes occurring within the cell membrane, the dependence on surf a c e a rea likely has a mechanistic basis. Activity decreases with attached bacteria have also been observed in batch assays by other workers [5,25]. Jeffery and Paul [5] found that the thymidine incorporation rate and the ATP/DNA ratio of free suspended cells were greater than those of attached cells.…”
Section: Degradation and Mineralization Of Naphthalene By Attached Cesupporting
confidence: 54%
“…Activity decreases with attached bacteria have also been observed in batch assays by other workers [5,25]. Jeffery and Paul [5] found that the thymidine incorporation rate and the ATP/DNA ratio of free suspended cells were greater than those of attached cells. They ascribed the reduced rates to physiological diff e rences between the two systems, primarily a re d u ction in the amount of cell surface available for nutrient uptake.…”
Section: Degradation and Mineralization Of Naphthalene By Attached Cesupporting
confidence: 54%
See 1 more Smart Citation
“…Note that MUSCHENHEIM et al (1989) found evidence that bacteria attached to particles from smooth-cordgrass shoots moved to the water column in laboratory incubations. Cells having just left the surface of decomposing leaves, where both leaf lysates and algal exudates (FALLON et al, 1985) could be available, might reasonably be expected to be more productive (thymidine incorporation per cell) than most of those in the bacterioplankton (see, e.g., JEFFREY and PAUL, 1986;TURLEY, 1993;AZAM et af., 1994;HEISSENBERGER et al, 1996;SCHUT et al, 1997). Cell emigration might also be involved in the explanation of changes in bacterial morphotypes during tidal excursions onto the marsh (NEWELL and KRAMBECK, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, for example, it was customary to measure ATP in the firefly bioluminescence assay by integrating light emission for 1 min or more (Holm-Hansen and Booth 1966), often beginning 5-15 s after the mixing of reagents (e.g. Jeffrey and Paul 1986) . Karl (1978), however, showed that this procedure can overestimate ATP concentrations by more than a factor of 2 due to the presence of non-adenine nucleotide triphosphates in microorganisms.…”
Section: Discussionmentioning
confidence: 99%